2004
DOI: 10.1080/00380237.2004.10571252
|View full text |Cite
|
Sign up to set email alerts
|

Majority Rules? The Effects of School Ethnic Composition on Substance Use by Mexican Heritage Adolescents

Abstract: This article examines key aspects of the school environment -its composition by ethnicity and acculturation -as important social contexts for understanding Mexican immigrant and Mexican American adolescents' drug use norms and behaviors. Results are presented based on surveys completed by Mexican-background students from 35 Phoenix. Arizona middle schools, whose enrollment ranged from a numerical minority to an overwhelming majority. Multivariate mixed models tested for the influence of school ethnic compositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…Similarly, research that distinguishes neighborhood and school context promises to be informative. In other research we have explored how school context influence individual substance use (Kulis, Marsiglia, Nieri, Sicotte, and Hohmann-Marriott, 2004). A logical next step is to examine how school and neighborhood influences operate in tandem to influence youth outcomes.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, research that distinguishes neighborhood and school context promises to be informative. In other research we have explored how school context influence individual substance use (Kulis, Marsiglia, Nieri, Sicotte, and Hohmann-Marriott, 2004). A logical next step is to examine how school and neighborhood influences operate in tandem to influence youth outcomes.…”
Section: Limitationsmentioning
confidence: 99%
“…The influence of highly motivated immigrant populations may be protective, as demonstrated by findings that drug use is less prevalent among Latinas living in communities with fewer highly acculturated individuals (Finch, Boardman, Kolody & Vega, 2000). Studies at the school level show lower rates of drug use among less acculturated Mexican Americans students who are in schools with high proportions of peers like themselves (Kulis, Marsiglia, Nieri, Sicotte, & Hohmann-Marriott, 2004), as well as a school level "immigrant advantage" in outcomes as diverse as academic failure and obesity (Crosnoe and Lopez-Gonzales, 2005).…”
Section: Parochial and Public Social Control: Immigrant Enclaves Segmentioning
confidence: 99%
“…Schools tend to be less communally oriented and more disorderly as rates of school and community poverty, teacher turnover, and male students increase (Akiba, 2008;Payne, Gottfredson, & Gottfredson, 2006). Moreover, critical densities of ''at risk'' students may interfere with the enactment of effective school processes and programming (Berliner, 2006;Kulis, Marsiglia, Nieri, Sicotte, & Hohmann-Marriott, 2004;Marsiglia, Kulis, Hecht, & Sills, 2004;Sebring et al, 2006). There is also interesting evidence that female principals may have somewhat greater capacity to enact communal school climates and to promote collaborative problem solving in schools (Blackburn, Martin, & Hutchinson, 2006).…”
Section: School Climate and Compositional Characteristicsmentioning
confidence: 94%
“…It is also quite possible that the both staff perceptions and school organization are impacted very heavily by the sheer number of risky peer groups on campus. There is growing evidence that critical densities of school and neighborhood poverty and at-risk students ''grind down'' the staff, generate demoralization and organizational dysfunction, and, ultimately, make it very difficult for schools to improve or enact effective programming over time (Berliner, 2006;Kulis et al, 2004;Marsiglia et al, 2004;Sebring et al, 2006). Theoretically, it is possible that both organizational dysfunction and risky peer groups represent a cyclical dynamic over time (e.g., one influences the other over time).…”
Section: Risky Peer Behaviors Drive Staff Congruence In Awareness Of mentioning
confidence: 96%
“…Prior research has demonstrated that interventions created by and for mainstream students, based on dominant culture values and beliefs, were not effective when applied to ethnically distinct groups (Forgey, Schinke, & Cole, 1997;Holleran et al, 2002;Kulis, Marsiglia, Nieri, Sicotte, & Hohmann-Marriott, 2004;Marsiglia, Kulis, & Hecht, 2001). Other studies underscored the need for researchers to understand what it means to be a member of an ethnically distinct group before attempting to develop prevention messages for members of those groups (Marsiglia, Miles, Dustman, & Sills, 2002;Napoli, Marsiglia, & Kulis, 2003;Okamoto, Hurdle, & Marsiglia, 2002;Sheets, 2003).…”
Section: Project Foundationsmentioning
confidence: 99%